Anatomical analysis of different helical plate designs for distal femoral fracture fixation. (1st June 2022) - Pastor, T; Beeres, F J P; Kastner, P; Gehweiler, D; Miglorini, F; Nebelung, S; Scaglioni, M F; Souleiman, F; Link, B-C; Babst, R; Gueorguiev, B; Knobe, M
Abstract: Objective: Helical plates potentially avoid the medial neurovascular structures of the thigh. Recently, two plate designs (90°- and 180°-helix) proved similar biomechanically behavior compared to straight plates. The aims of this study were: (1) feasibility of applying 90°- and 180°-helical plates in MIPO-technique to the femur, (2) Assess the distances to adjacent anatomical structures which are at risk, (3) Compare these distances with medial straight plates, and (4) Correlate measurements performed during anatomical dissection with CT-angiography. Methods: MIPO was performed in ten cadaveric femoral pairs using either a 90°-helical 14-hole-LCP (group1) or a 180°-helical 15-hole-LCP-DF (group2). Using CT-angiography, distances between femoral arteries and plates as well as distances between plates and perforators were evaluated. Following, specimens were dissected, and distances determined again. All plates were removed, and all measurements were repeated with straight medial plates (group3). Results: Closest overall distances between plates and femoral arteries were 15 mm(11–19 mm) in group1, 22 mm(15–24 mm) in group2 and 6 mm(1–8 mm) in group3 with a significant difference between group1 and group3(p<0.001). Distances to the nearest perforators were 24 mm(15–32 mm) in group1 and 2 mm(1–4 mm) in group2. Measurement techniques (visual after surgery and CT-angiography) showed a strong correlation of 0.972(p<0.01). Conclusion: MIPO with 90°- and 180°-helical plates is feasible and safe. Attention must be paid to the medial neurovascular structures with 90°-helical implants and to the proximal perforators with 180°-helical implants. Helical implants can avoid medial neurovascular structures compared to straight plates although care must be taken during their distally insertion. Measurements during anatomical dissection correlate with CT-angiography.